The Promotion of Extracurricular Sports Clubs on College Physical Education---------- Taking China West Normal University as Example - Xiufang, Wei (Social Science Learning Education Journal, 2017)
In recent years, upon deepening the reform on physical education (PE) curriculum in collegesï¼colleges in many areas have established sports clubs. It makes PE class teaching and the after-PE class extension be fully combined, promotes the reform of PE curriculum, enhances the teaching efficiency and the sports level of college students, cultivates college studentsâ life habits of consciously doing sports exercises, and finally provides a solid foundation for studentsâ life-long sports. Taking the extracurricular sports club teaching of China West Normal University as the starting point, this paper tries hardly to explore the innovative models of physical education (PE) curriculum reform of schools and to provide references for other colleges.